PROTOTYPE OF AIR PURIFIER TO REDUCE AIR CONTAMINANTS AND ELIMINATE INSECTS BASED ON ESP32 AT UNIVERSITAS HARAPAN MEDAN - Rivaldi, Rivaldi (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2022)
Lifestyles have undergone significant changes; people spend more time indoors, and poor air quality occurs not only outdoors but also potentially indoors. According to the EPA, indoor pollution is in the third position of environmental factors affecting human health. in order to meet the need for cleaner air than before, the existing air filtration system is an important thing to pay attention to. Handling the filtration method to deal with pollutants will be a long-term requirement. The problem studied in this study is how to build an air filtration system in a room that can work efficiently without having to replace the filter media such as a HEPA filter, the design of this tool does not use a HEPA filter in general but uses dew dispersion from a mist maker, this tool is designed to be able to capture air particles and combine them with particles of air. This tool is designed to be able to display the value of CO2 conductivity, temperature, and humidity through an application on an Android device and an LCD on an air purifier device.